Analisis Dana Talangan Haji Berdasarkan Fatwa No.29 / DSN-MUI / VI / 2002 (Studi Kasus Pada BPRS Dana Mulia Surakarta) - Muhammad Tho'in; Iin Emy Prastiwi (Jurnal Ilmiah Ekonomi Islam, 2016)
Recently, there are many Islamic Finance Institutions (LKS) offer  a product to help moslem to register for the fortfcoming haji session although they didn’t have enough money. This product is called “Dana Talangan Haji”. BPRS Dana Mulia uses ijarah multijasa contract for giving hajj credit. So that, researcher interested to take a research about the Implementation of Hajj credit financing at BPRS Dana Mulia.The aim of the research is to know the Implementation of Hajj credit financing at BPRS Dana Mulia and to analyze the relevance with DSN-MUI Fatwa No.29/DSN-MUI/VI/2002 about Hajj Credit Financing by Islamic Finance Institutions (LKS). The kinds of this research is field research. While the method used for collecting data consist of observation, interview and documentation. For the analisis technique, researcher uses descriptive qualitative approach.From this research, researcher finds that the implementation of Hajj Credit financing at BPRS Dana Mulia Surakarta is not relevant with Fatwa No.29/DSN-MUI/VI/2002 about Hajj Credit Financing by Islamic Finance Institutions (LKS) because BPRS Dana Mulia uses ijarah multijasa contract that based on fatwa DSN-MUI NO. 44/DSN-MUI/VIII/2004 about multijasa financing.Keywords: Islamic Finance Institutions (LKS), ijarah multijasa, fatwa